2020
DOI: 10.1155/2020/7457902
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-Chamber Phakic Intraocular Lens Implantation in Patients over 40 Years of Age

Abstract: Purpose. To assess the efficacy, safety, and predictability of the Visian Implantable Collamer Lens (ICL) model having a central port in patients over 40 years of age. Methods. This study included 33 eyes from 21 patients who underwent V4c ICL implantation for the correction of myopia and myopic astigmatism. We assessed uncorrected (UDVA) and corrected (CDVA) distance visual acuity, refraction, intraocular pressure (IOP), endothelial cell density (ECD), vault, and adverse events occurring over a 1-year period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Previous research findings from a 3-year follow-up of 184 eyes of 92 patients indicated indices of 1.03 and 0.90, respectively, 16 while a recent study involving a 1-year follow-up after ICL V4c implantation in patients >40 years confirmed that the two indices were 1.09 and 1. 17 In the current study, the safety indices at the three postoperative follow-up time points were not statistically different. Intriguingly, significant differences in efficacy index were found between 3 months postoperatively and at last follow-up.…”
Section: Discussioncontrasting
confidence: 48%
“…Previous research findings from a 3-year follow-up of 184 eyes of 92 patients indicated indices of 1.03 and 0.90, respectively, 16 while a recent study involving a 1-year follow-up after ICL V4c implantation in patients >40 years confirmed that the two indices were 1.09 and 1. 17 In the current study, the safety indices at the three postoperative follow-up time points were not statistically different. Intriguingly, significant differences in efficacy index were found between 3 months postoperatively and at last follow-up.…”
Section: Discussioncontrasting
confidence: 48%
“…With the clinical application of ICL with a central hole (hole ICL), or ICL V4c, the misgivings regarding possible effect of ICL on cataract formation in the elderly population have been dispelled as it improves aqueous humor circulation [ 6 , 7 ]. ICL V4c is also safe for the correction of ametropia in myopic people aged 40 years or above [ 8 ]. ICL V4c implantation is reversible; therefore, its application in monocular refractive surgery is worthy of further study.…”
Section: Introductionmentioning
confidence: 99%
“…In this multicenter study, the patients were aged 45 years or older and were at a high risk of developing cataract with conventional ICL 4 . There are only a few reports 6 8 on the postoperative outcomes after hole ICL implantation in middle-aged and older patients, which are summarized in Table 5 . All previous reports 6 8 had short observation periods and small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports 6 8 on the postoperative outcomes after hole ICL implantation in middle-aged and older patients, which are summarized in Table 5 . All previous reports 6 8 had short observation periods and small sample sizes. In this study, the mean observation period was 2.2 years (cases with more than 1 year of follow-up), and the safety index was 1.08.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation